Impact of abattoir effluents on surface waters of the Alamuyo stream in Ibadan - NK Raheem; OA Morenikeji (Journal of Applied Sciences and Environmental Management, 2010)
Physico-chemical analysis were carried out on samples collected from four sampling stations located along a stream that receives effluent discharge from an Abattoir in Ibadan, Nigeria using standard methods. The data revealed that the effluent discharge had high temperature (33.48±0.354oC); H+(7.70±0.86); TDS(2363±166.46mg/l); TSS(11032±424.95mg/l); BOD(3898±150.78mg/l);  COD(6738.5±204.43mg/l); total hardness v(448.25±33.51mg/l); SO4 2-(15.303±0.389mg/l); NO3 -(24.13±0.593mg/l); PO4 3-(5.283±0.221mg/l); b NH3(76.14±0.938mg/l); Ca(63.33±2.4041mg/l); (375±33±5.175mg/l);Na(975±27.54mg/l); Fe(5.52±0.44mg/l); Mn(0.433±0.092mg/l) and Zn(0.307±0.020mg/l). DO was not detected in the effluents. Comparison of the water physico-chemical status and the abattoir effluent load indicates that, there seem to be pollutional stress of the stream.